The Indian Evidence of Nexus between Economic Growth and Innovation - K. P., Dr. Radhika; D, Dr. Bhuvaneshwari (Journal of Contemporary Research in Management (JCRM), 2021)
The relationship between innovation and economic growth has been extensively studied in the literature, with numerous authors highlighting the positive impact that innovation can have on economic performance. In India, this relationship is particularly relevant, as the country has experienced significant economic growth in recent years and is widely recognized as one of the world’s leading innovation hubs. One key factor contributing to India’s economic growth has been the country’s investment in research and development. According to the National Science and Technology Management Information System (NSTMIS), India’s spending on research and development as a percentage of GDP has grown from 0.7% in 2006 to 1.2% in 2016 (NSTMIS, 2016). This increase in investment has helped to create an environment that is supportive of innovation and has provided the resources necessary for firms to pursue new and cutting-edge technologies. This paper is an attempt to examine the causal relationship between economic growth and innovation in India for the period 2001 to 2020. Research and Development Expenditure (% of GDP) and the number of patents filed by Indian Residents are the innovation indicators that are examined for causality with the per capita economic growth of India. The Granger Causality Test was used to determine the direction of causality between innovation and economic growth. The findings of the study suggest that innovation plays a crucial role in the economic growth of the country and supports the body of economic theory, which states that “economic growth is the result of appropriate knowledge, innovation, and entrepreneurship operating within an institutional environment of systems of innovation.